Aplicação de "multilocus sequence analysis" (MLSA) para identificação de linhagens de "Chromobacterium" sp : Application of "multilocus sequence analysis" (MLSA) for lineages identification of "Chromobacterium" sp - Borges, Isadora Vitti Vieira, 1991- (2018)
Orientador: Fabiana Fantinatti Garboggini